2020
DOI: 10.12968/bjcn.2020.25.6.294
|View full text |Cite
|
Sign up to set email alerts
|

Social prescribing: a ‘natural’ community-based solution

Abstract: This paper discusses social prescribing as part of the wider NHS England universal personalised care model, and it describes how community nurses can engage with social prescribing systems to support community resilience. A case study based on the example of gardening, as a nature-based social prescription provided by the RHS Bridgewater Wellbeing Garden, is provided to illustrate the scope, reach and impact of non-medical, salutogenic approaches for community practitioners. The authors argue that social presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 25 publications
2
48
0
6
Order By: Relevance
“…This is partly consistent with previous literature, as health and sustainability motivations have been highlighted as reasons for taking part in UA (Al-Mayahi et al, 2019;Martinho da Silva et al, 2016;Ruggeri et al, 2016), and these motivations for food choices are associated with healthy eating attitudes (Sun, 2008). UA may also act as a potential health promotion intervention (Brown & Jameton, 2000;Genter et al, 2015;Howarth et al, 2020), and our findings suggest that specifically incorporating and targeting health and ethical-related food choice motivations within such interventions may facilitate UA's beneficial impact on diet quality Contrary to our hypothesis, greater perceived access to fruits and vegetables was associated with a poorer quality diet. This is surprising as others have shown that such access is associated with increased fruit and vegetable consumption (Caldwell et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is partly consistent with previous literature, as health and sustainability motivations have been highlighted as reasons for taking part in UA (Al-Mayahi et al, 2019;Martinho da Silva et al, 2016;Ruggeri et al, 2016), and these motivations for food choices are associated with healthy eating attitudes (Sun, 2008). UA may also act as a potential health promotion intervention (Brown & Jameton, 2000;Genter et al, 2015;Howarth et al, 2020), and our findings suggest that specifically incorporating and targeting health and ethical-related food choice motivations within such interventions may facilitate UA's beneficial impact on diet quality Contrary to our hypothesis, greater perceived access to fruits and vegetables was associated with a poorer quality diet. This is surprising as others have shown that such access is associated with increased fruit and vegetable consumption (Caldwell et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…In our exploratory analysis we saw that scores for engagement with UA, not proximity to UA, were associated with greater psychological distress (Tables S4, S6), which may support this. This would fit with recent suggestions that gardening could be beneficial treatment for poor well-being (Howarth et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Isto contribui para que as ocupações não sejam apenas preenchidas, mas que gerem constantemente um repertório de significados para o indivíduo, baseando-se no universo que este se encontra e a volição das atividades que norteiam os desejos e as vontades da pessoa 24 25 . Howarth et al (2020) 26 identificou em seu estudo que a prescrição social de soluções baseadas na natureza que promovem a saúde e o bem-estar são cada vez mais incomuns nas rotinas das pessoas que estão em isolamento social e consequentemente tem acarretado nesses indivíduos ansiedade e a obrigatoriedade de ser resiliente 26 .…”
Section: Resultados E Discussõesunclassified
“…18 Finally, 'social prescribing', where people are referred to non-clinical services, support groups and social structures, can be helpful for people experiencing mental health issues, chronic physical health conditions or social isolation. 20,21…”
Section: Management Fostering Resiliencementioning
confidence: 99%